A Computerized Data Base System for S&T Resources - Kopr Kritayakirana; Chairat Jitkaew; Piengjit Chaiyasut; Wanna Patraplapibul; Prayoon Shiowatana (ASEAN Journal on Science and Technology for Development, 1987)
A Computerized Data Base System for S&T Resources